2020
DOI: 10.3389/fmicb.2020.00682
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Climate Induced Increase in Soil Water Availability for Soil Bacterial Communities Exposed to Long-Term Differential Phosphorus Fertilization

Abstract: The fate of future food productivity depends primarily upon the health of soil used for cultivation. For Atlantic Europe, increased precipitation is predicted during both winter and summer months. Interactions between climate change and the fertilization of land used for agriculture are therefore vital to understand. This is particularly relevant for inorganic phosphorus (P) fertilization, which already suffers from resource and sustainability issues. The soil microbiota are a key indicator of soil health and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 117 publications
(141 reference statements)
0
3
0
Order By: Relevance
“…Sandy soils require more frequent irrigation than silty soils with larger PASW storage capacity. For natural systems, the concept of PASW has been used in ecological studies (Liu et al., 2009; Randall et al., 2020) to investigate how soil modulates climatic inputs or forcing affecting vegetation. In other words, PASW is not used for “design” or crop selection, but for interpretation of natural vegetation response to climatic conditions or changes in rainfall patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Sandy soils require more frequent irrigation than silty soils with larger PASW storage capacity. For natural systems, the concept of PASW has been used in ecological studies (Liu et al., 2009; Randall et al., 2020) to investigate how soil modulates climatic inputs or forcing affecting vegetation. In other words, PASW is not used for “design” or crop selection, but for interpretation of natural vegetation response to climatic conditions or changes in rainfall patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Under controlled environments, P fertilization has been found to have a more prominent effect on acid and alkaline phosphatase enzyme activities than soil moisture or temperature (Randall et al, 2020;Sun et al, 2018). However, field studies conducted in intensively managed agroecosystems and grasslands showed that seasonal changes in soil moisture and temperature had a more significant impact on alkaline phosphatase enzyme activity compared with P fertilization (Shi et al, 2013(Shi et al, , 2020.…”
Section: Effects Of Seasonal Conditions On Organic Soil P Cyclingmentioning
confidence: 99%
“…Perrott et al (1992) found that microbial biomass P increased with increasing soil moisture in a low P grassland soil, whereas He et al (1997) described no clear relationship between microbial biomass P and air temperature in both unfertilized and P fertilized pasture systems in the United Kingdom. On the other hand, Randall et al (2020) pointed out a significant response of acid phosphatase activity to historical soil P status but not of water availability in soils taken from a long‐term P fertilization experiment under pastures. A more refined understanding of P immobilization and mineralization processes as affected by soil moisture, temperature, and P availability is needed to better predict organic P cycling, especially under future scenarios of climate change.…”
Section: Introductionmentioning
confidence: 99%